CONFIRMATION OF THE DE POLIGNAC AND THE TWIN PRIMES CONJECTURES (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
I show the veracity of the De Polignac conjecture, remained open since 1849, which says that for any natural integer k there is an infinite number of pairs of prime integers differing by 2k, and I deduce the twin prime conjecture (i.e. the case k=1) . I do this by using the Schoenfeld inequality that I have proved in [10] and by using the same approach that I have used in [11].